Descartes’ Sum-Res-Cogitans-Argument in der Zweiten Meditation - Dierig, Simon (Archiv für Geschichte der Philosophie, 2022)
Two major interpretations have been advanced for the sum res cogitans passage in Descartes’s Second Meditation. According to the first interpretation, he argues in this passage that only thinking belongs to his essence. According to the second interpretation, due to Anthony Kenny, Harry Frankfurt and others, no such claim is defended by Descartes. Rather, it is his aim to argue that only thinking can be ascribed to him with certainty. In this essay, it will be shown that the “naive”, essentialist reading of the sum res cogitans reasoning is closer to the text than the perhaps more sophisticated, purely epistemic reading. Although the interpretation defended here is not new, it will be arrived at by way of (hopefully) new arguments.
Gesehen am 22.12.23